Pelatihan Pembukuan Akuntansi Sederhana Terhadap Pelaku Usaha Kecil di Kampung Cibodas Tangerang - Nurjannah Nurjannah; Annisa Fauziah; Nandya Atiasya Lutfiani; Siti Ripda Saripah; Ulfah Ulfah; Yohana (Institut Nalanda, 2024)
Real Work Lectures (KKN) as a form of higher education service to the community are implemented in Cibodas Village, Tangerang. The focus is to provide simple accounting bookkeeping training to small businesses, especially small stall traders in the area. The methods used involve surveys, outreach, and training using the